2009
DOI: 10.3155/1047-3289.59.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Exhaust Emission Factor Measurements on Chassis Dynamometer

Abstract: To improve the accuracy, reliability, and representativeness of emission factors, 10 European laboratories worked together to study the influence of 20 parameters on the measurement of light-vehicle emission factors on chassis dynamometer of 4 main categories: driving patterns, vehicle-related parameters, vehicle sampling, and laboratory-related parameters. The results are based on (1) literature synthesis, (2) approximately 2700 specific tests with 183 vehicles, and (3) the reprocessing of more than 900 tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…40,51 The vehicle sample size per laboratory was only around 3-11. However, Joumard et al 52 observed that the minimum vehicle sample size to build-up a representative model of average emissions is 10 vehicles. The global load of 460 kg including the driver corresponds to loads of 60 and 49% respectively for the tested gasoline and diesel vehicles.…”
Section: Emission Factor Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…40,51 The vehicle sample size per laboratory was only around 3-11. However, Joumard et al 52 observed that the minimum vehicle sample size to build-up a representative model of average emissions is 10 vehicles. The global load of 460 kg including the driver corresponds to loads of 60 and 49% respectively for the tested gasoline and diesel vehicles.…”
Section: Emission Factor Calculationmentioning
confidence: 99%
“…These low emissions of NO x are probably due to the low acceleration observed during the tests because of the road environment and the high load rate, which does not facilitate high acceleration. Osses et al 57 showed that NO x are better correlated with positive acceleration rather than speed for noncatalyzed vehicles and Joumard et al 52 demonstrated that NO x and CO 2 LDV emissions are very sensitive to the acceleration frequency and high acceleration.…”
Section: Hot Emissionsmentioning
confidence: 99%
“…For improving the reliability of the Dynamometer tests, a research has been done by 10 European laboratories to study the influence of 20 parameters in the dynamometer testing on the emission factors of light duty vehicle [24]. These factors included driving patterns, vehicle related parameters, sampling, and parameters related to laboratory.…”
Section: A Dynamometer and Driving Cycle Testingmentioning
confidence: 99%
“…It makes no sense to climb the smokestack with 1950s-era glass impingers to separately measure NO x , SO 2 , PM 10 , etc., as required by EPA's certification source testing methods. 166 It is time to replace these antiquated practices with a dilution system, similar to that used for mobile sources, 109,[167][168][169][170][171][172] to which ambient sampling and analysis methods can be coupled. 173 …”
Section: Invited Comments By Dr John Watsonmentioning
confidence: 99%